"I want to play a normal game. I don't need all this." - Carina de Assunção; Michael Scott; Rory Summerley (Eludamos)
Esports in Portugal have been growing steadily in recent years. As in many other countries, women are significantly underrepresented in Portuguese esports. New studies with Portuguese students show conservative views towards gender roles and disinterest in prioritising diversity, equity, and inclusion (DEI), which contrasts with the global tendency to incorporate it in the industry. Lately, initiatives promoting DEI have populated the esports landscape. However, the communities’ response, which may impact effectiveness, remains under-examined. This work is part of a larger ethnographic project that aims to understand how the esports communities in Portugal perceive and react to DEI initiatives such as women-only tournaments or harassment awareness campaigns. This paper will discuss findings from the thematic analysis of 10 interviews with Portuguese members of an esports community. The recurring themes were (1) DEI initiatives are imposed; (2) Portugal is too small to care (about DEI); (3) nepotism; (4) self-preservation; and (5) ubiquity of online toxicity.